2011
DOI: 10.1109/tns.2010.2090899
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Sensor for In-Pile Fuel Rod Fission Gas Release Measurement

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As a result, the gas sensors employed should have long-term stability under the nuclear radiation. It is reported that acoustic wave gas sensors can survive and keep a long-term sensitivity under nuclear radiation with a maximum operating temperature of 140°C [31] , however, the research on the gas sensors under nuclear radiation is still under development and requires further efforts to build it up.…”
Section: Nuclear Facilitiesmentioning
confidence: 99%
“…As a result, the gas sensors employed should have long-term stability under the nuclear radiation. It is reported that acoustic wave gas sensors can survive and keep a long-term sensitivity under nuclear radiation with a maximum operating temperature of 140°C [31] , however, the research on the gas sensors under nuclear radiation is still under development and requires further efforts to build it up.…”
Section: Nuclear Facilitiesmentioning
confidence: 99%
“…The speed of the wave depends, among other things, on the atomic composition of the gas. The theoretical principle of sensor operation was demonstrated experimentally in 2010 in the OSIRIS reactor (CEA Saclay, Paris) by a sensor named CACP-1 [3], [4]. The principle of the measurement was to monitor gaseous releases from fuel pellets, which are either MOX or UO2, during reactor operation.…”
Section: • a Volume Of Less Than 3cm3mentioning
confidence: 99%
“…and bonding techniques, to develop a dedicated ultrasonic transducer in the MHz frequency range (typically 4 MHz). A selection was made after carrying out preliminary gamma irradiation tests (CEA facility, 1.5 MGy), mixed gamma and neutron irradiation tests in SCK•CEN BR1 reactor [144], and a full-scale device with PZT (Lead Zirconate Titanate piezoelectric ceramic) was successfully tested during a two-year exposure in hot cell surroundings at CEA LECA-STAR facility [145]. In the REMORA 3 experiment in OSIRIS reactor [146] at 144°C max with a PZT transducer, signal degradations were observed in phase 1 for high neutron fluences: ∼10 19 thermal n/cm 2 , 2.5 Â 10 18 epithermal n/cm 2 , 2.4 Â 10 18 fast n/cm 2 according to the revised data given in [147].…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…In some cases assessments have been made directly in real conditions in a power reactor (TUSHT of Sonar device in Phenix reactor), as long as it was possible. In other cases, they are performed in experimental or research reactors in France (OSIRIS), Belgium (BR1, BR2), Norway (HBWR), USA (ATR), for example [25,82,144,146,147,[150][151][152][153][154][155]. Some convenient experimental adaptations may be necessary to perform remote electric and acoustic measurements via mechanical bounding to a delay line, and to control the experimental conditions (irradiation, temperature), within volume limitations.…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
See 1 more Smart Citation